Universal secondary education in the OECS : some views on the curriculum - King, Winston K. (2009)
Notes that various international initiatives in education, followed by the development of the Organization of Eastern Caribbean States Reform Strategy led to initiatives in Universal Secondary Education in the countries of the sub-region. Indicates that several obstacles have been identified and suggests that there needs to be more monitoring, evaluation and support of various types to make the reform effective and sustainable.